Akuntansi Manajemen sebagai Pilar Pengambilan Keputusan dan Daya Saing Bisnis di Tengah Tantangan Digitalisasi - Bancin, Jusuf Sugiarto; Yohanes Waruwu; Rahel Oktavia Sinaga; Indah Putri Sari Pardosi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The rapid digital transformation has driven fundamental changes in management accounting practices, making it not only a tool for recording and controlling costs, but also a strategic foundation for decision-making and improving corporate competitiveness. This study aims to examine the role of management accounting in decision-making, cost efficiency, and improving organizational performance, both in the corporate sector and Micro, Small, and Medium Enterprises (MSMEs), by integrating findings from ten recent scientific articles. The method used is a literature study (library research) with a qualitative-descriptive approach. The results of the analysis show that management accounting contributes significantly to the effectiveness of decision-making, especially when combined with information technology and adaptive business strategies. Digitalization of accounting information systems has been shown to improve operational efficiency, data accuracy, and organizational responsiveness to market dynamics. However, the success of implementing modern management accounting is greatly influenced by human resource competency, technological infrastructure readiness, and contingency factors such as company size and external environment. This study emphasizes the importance of the role of management accounting in supporting business sustainability in the digital era and provides recommendations for organizations to integrate technology-based accounting systems, strengthen HR capacity, and formulate business strategies that are in line with managerial information needs. These findings are relevant for practitioners, academics, and policy makers in an effort to build an adaptive and data-based decision-making system amidst rapid changes in the business environment.